IDENTIFIKASI PENYEBAB TIDAK OPTIMALNYA PENANGANAN PEMBIAYAAN BERMASALAH DI KSPS BMT ABC CABANG PEMBANTU KLM-SURABAYA - Martha Dyah Puspita; Dian Filianti (Universitas Airlangga, 2019)
Sharia Financial Services Cooperative (KJKS) is a form of cooperative whose business activities are engaged in financing, investment, and deposits in accordance sharia principles. in relation to financial services in the form of such financing, in this case the Sharia Financial Services Cooperative (KJKS) will be faced with several risks, among others, is the risk of default on financing channeled and the existence of fraud action (fraud) committedby the management of the financial institution. The object of this research is KSPS BMT ABC Branch KLM-Surabaya.on the object of the study found that the total gross NPF until December 2016 reached 81.84%, in addition to the impact of high levels of Gross NPF is a loss to be borne until December 2016 amounted to Rp 354.715.664. Based on the results of pre-research interview with Mr. Muhammad stated that the cause of the loss due to there are two factors namely the existence of fraud (misconduct) in the form of misuse of funds by former employees and handling financing problems that can be optimally 30% of total troubled financing. The purpose of this study is to determine the cause of the non-optimal handling of troubled financing. Things that need to be reviewed in the process of handling pembiyaan problem is based on the phenomenon that occurs in the object of research. This research uses qualitative method with exploratory case study strategy. The results of research conducted by the researchers found that KSPS BMT ABC Branch KLM-Surabaya Assistant has a concept of mixing handling of non-performing financing based on standard operating procedures with the handling of troubled financing based on kinship.Keywords: Troubled Financing, Troubled Financing Handling, FraudREFERENCES Antonio, Muhammad Syafi’i. 2001. Bank syariah: Dari teori ke praktik. Jakarta.Baharuddin, Kalyisah. 2013. Penerapan Prinsip Kekeluargaan Dalam Penyelesaian Pembiayaan Bermasalah Pada BMT Al-Amin Makasar. Skripsi. Makasar: Fakultas Ekonomi Dan Bisnis Universitas Hasanudin.Baharudin, S. 2013. Koperasi Syariah dan Pengaturanya di Indonesia. Karim A, Adiwarman. 2014. Bank Islam: analisis fiqih dan keuangan. Jakarta.KSPS BMT ABC. 2017. Pedoman Rapat Anggota Tahunan KSPS BMT ABC tahun 2016. Pasuruan.Moleong, lexy J. 2009. Metode penelitian kualitatif. Bandung.Shihab M Quraish. 2002. Tafsir Al – Misbah, Jakarta.Subagyo, Ahmad. 2015. Manajemen Operasi Lembaga Keuangan Mikro Syariah. Jakarta.Subagyo, Ahmad. 2015. Teknik Penyelesaian Kredit Bermasalah. Jakarta.Sugiyono, Prof. Dr. 2009. Metode penelitian kuantitatif, kualitatif, dan R&D. Bandung.Suhendi, Hendi. 2002. Fiqh Muamalah, edisi 9. Jakarta.Usanti, Trisandini P. 2006. Restrukturisasi Pembiayaan Sebagai Salah Satu Upaya Penanganan Pembiayaan Bermasalah. Vol IX, No III.Usanti, Trisandini P dan Abd Shomad. 2015. Transaksi Bank Syariah. Jakarta: Bumi AksaraYin, Robert K. 2015. Studi Kasus Design & Metode. Jakarta: Raja Grafindo Persada